Exploring the Use and Effectiveness of Speech Acts by EFL High School Teachers - Ida Bagus Nyoman Mantra; Ida Ayu Made Sri Widiastuti; Dewa Ayu Ari Wiryadi Joni (Journal on Studies in English Language Teaching (JOSELT), 2026)
This study investigated the use of speech actions by English as a foreign language (EFL) high school teachers and their usefulness in improving classroom communication. Data were gathered from 20 EFL high school teachers through interviews and classroom observations. The study found that speech actions are essential for regulating classroom activities and improving students' language skills. The data analysis found that teachers with higher levels of English proficiency could employ a broader range of speech acts, and teachers' communicative styles influenced the types and frequency of speech acts used. The findings imply that teacher training programs should prioritize the development of successful communication skills, such as speech acts, to improve teacher effectiveness in the classroom. The study emphasizes the relevance of excellent communication skills in language education and the need for continual training and professional development to improve teacher effectiveness. These findings have significant implications for language teacher education programs and the development of practical communication skills among language teachers.